Hello snigdha Originally Posted by
snigdha Find the Mean Proportion:
(a+b)* (a-b)^3 , (a+b)^3 *(a-b)
The Mean Proportion of two numbers is, I think, what is more usually called the Geometric Mean, and is the square root of their product. So if $\displaystyle b$ is the mean proportion of $\displaystyle a$ and $\displaystyle c$, then$\displaystyle b^2 = ac$ or $\displaystyle b = \sqrt{ac}$
So here the mean proportion is$\displaystyle \sqrt{(a+b)(a-b)^3(a+b)^3(a-b)}$$\displaystyle =\sqrt{(a+b)^4(a-b)^4}$
$\displaystyle =(a+b)^2(a-b)^2$
which could be written as
$\displaystyle =(a^2-b^2)^2$
Grandad